Mucin producing microfollicular adenoma of the thyroid. - Rigaud, C (1985)
An unusual case of a mucin secreting benign microfollicular adenoma of the thyroid in a 30 year old euthyroid woman is reported. Histologically, the lesion was characterised by follicular cells with the appearance of signet ring cells. Histochemistry showed the mucin content of these cells to consist uniformly of sulphated acid mucins; positive thyroglobulin immunostaining was also shown. The published work on primary mucin secreting tumours of the thyroid gland is reviewed. Dual differentiation is thought to be responsible for combined mucin secretion and hormone production in this type of neoplasm.